The role of women in enhancing economic standards in rural areas through the implementation of waste reform in Desa Cemagi - Ni Wayan Mekarini; Ni Nyoman Arini; Sulistyoadi Joko Saharjo; Aerial Yeremia Jumadi; Jaka Nur Hidayat; I Gede Kesuma Arimbawa; I Nyoman Komang Adi Saputra; Charisa Gracia Ola; Maria Angelia Selvira Foglin; Frederika Banyo; Kristina Rati Ratna; Maria Agusta Hipolita Ampur; I Made Ari Sedana (Universitas Muhammadiyah Magelang, 2024)
Cemagi Village faces challenges in its human resources sector, which are not yet prepared to compete in the tourism industry, and waste management, which is deemed highly risky. In response to waste management issues, the Cemagi Village Perbekel has initiated the establishment of the Sarwa Metu Wangi TPS3R to oversee waste management and has appointed cadres to manage waste banks in each Banjar neighborhood. To address these issues, a pilot project was launched for women's empowerment activities in Cemagi Village, specifically in Banjar Sangiangan. These service activities aim to empower women in Cemagi Village by encouraging women's groups to actively sort waste, generate additional income from the sale of segregated waste, increase public awareness of the importance of proper waste management for environmental cleanliness and public health, and support tourism village development through the application of the Sapta Pesona principles. The method of implementing these activities involves conducting waste management awareness campaigns and providing assistance in waste sorting at residents' homes. The results of these activities indicate that the community has begun to actively sort waste in accordance with guidance provided by the implementation team during assistance. This is evident from the initial condition of waste deposits at the onset of waste bank activities, which were predominantly mixed or improperly sorted. However, after providing assistance at residents' homes, the waste brought to the waste bank has begun to be properly sorted. Changes in people's waste sorting behavior serve as an indicator of the success of awareness campaigns and mentoring efforts, reflecting an increase in public awareness regarding the importance of proper waste sorting for environmental protection.